(untitled) (South East Asia Journal of Public Health, 2014)
Girls have traditionally been neglected in India. The neglect is reflected in adverse sex ratio of 914 girls per 1000 boys as reported in 2011 census. The declining sex ratio can be prevented by the registration of female children and by ensuring their progress and safety. The study aims at finding the effect of the introduction of a conditional cash transfer scheme (Majoni scheme) upon the registration of a female child. It was a hospital record-based study where the preferential treatment of female children during registration into the birth register before and after the introduction of the Majoni scheme was measured. An effect of the scheme on the registration of male and female children was also compared. The introduction of this scheme increased the female to male ratio of applications for the registration of births from 1.06 to 1.34 and also increased the number of formal requests for the registration of the birth of a female child from 24.45% to 39.05%. Financial incentives or securities have been shown to modify human behavior. The increase in the numbers of applications for the registration of a female child, after the intro-duction of the Majoni scheme was due to the financial incentive attached with the registration. The increasing trend in the number of applications with every passing month was probably due to the increase in awareness regard-ing the benefit of the scheme. Conditional cash transfer schemes, such as Majoni, can have a significant effect on increasing the registration of female children. Further study is required to evaluate the effect of the factors other than the financial incentive upon the registration of female children. South East Asia Journal of Public Health 2013; 3(1): 30-35 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17708